Walking in nature may improve affect but not cognition - Trammell, Janet P.; Harriger, Jennifer A.; Krumrei-Mancuso, Elizabeth J. (Frontiers in Psychology, 2024)
Beneficial effects of natural environments on affect have been consistently reported, but effects on cognition have been less consistent. We examined affect and cognitive performance in the domains of attention, working memory, executive function, and recall and recognition memory in a sample of 188 undergraduate participants who completed a walk in one of three environments: an outdoor nature environment, an outdoor urban environment, or an indoor (treadmill) environment. Supporting the hypotheses, the outdoor nature environment resulted in the greatest increase in positive affect and decrease in negative affect from pre-to post-walk. However, there were no effects of location on any cognitive measure. These results suggest that cognitive effects do not always occur in tandem with affective benefits. Possible explanations, including prior frequent exposure to nature in our participants and extremity of the natural environment, are discussed.